Early Post-Operative Outcome and Complication of Arteriovenous Fistula Creation under Regional Anesthesia - Shrestha, Kajan R (Journal of Institute of Medicine Nepal, 2019)
Introduction Arteriovenous fistula (AVF) is the commonest vascular access for patients with end stage renal disease (ESRD) undergoing hemodialysis, however there is no consensus regarding mode of anaesthesia for creation of AVF. Mode of anaesthesia may have effect on outcome and complication of AVF. Methods This is a retrospective descriptive study conducted on the basis of data collected from patients undergoing AVF under brachial plexus block (BPB) from January 2018 to December 2018 at Manmohan Cardiothoracic Vascular and Transplant Center (MCVTC). Data regarding demographics, results and complications have been analyzed. Results A total of 79 patients (male: female=45:34) underwent AVF under BPB during one year period at University teaching hospital with a mean age group of 56.76±11.65 years (24-86 years). In three patients, the brachial plexus block failed and was substituted with general anaesthesia while 21 patients needed some adjuncts with block to create fistula. In 38 patients (48.10%) brachiocephalic fistula was created and in 48 patients (60.76%), plan to make fistula at proximal site was changed after application of block to more distal level. All fistulas were patent at 24 hours (100%, 79 patients) and the rate was 93.67% (74 patients) at 6weeks. The complications seen post procedure were limb oedema in five patients (6.33%), thrombosis and infection in one patient each, hematoma in two patients and bleeding in three patients. Conclusion Brachial plexus block is effective modality of anaesthesia to create AVF for hemodialysis as it increases chances of creating distal fistula and also increases the effectiveness of it.